Electron transport and visible light absorption in a plasmonic photocatalyst based on strontium niobate - D. Y. Wan (Nature Portfolio, 2017)
Metallic oxide SrNbO3has been identified as an efficient hydrogen evolution photocatalyst. Here, Venkatesan and co-workers show that its visible light absorption stems from plasmon resonance, thanks to its large carrier density (despite a large 4.1 eV bandgap), as opposed to from an interband transition.